PENYELESAIAN KASUS KECELAKAAN LALU LINTAS DI WILAYAH HUKUM KEPOLISIAN RESOR BANGLI MELALUI PELAKSANAAN RESTITUSI - Adhitya, Made Prawira (Kerta Dyatmika, 2023)
The handling of traffic accident cases in Indonesia is carried out by the Indonesian National Police through the traffic function, based on Law Number 22 of 2009 concerning Road Traffic and Transportation. Traffic accidents may result from either negligence or intentional conduct, both of which are subject to criminal sanctions, including imprisonment, as well as the obligation to provide restitution to victims. Over time, restitution has evolved into a basis for terminating case examinations; however, the effectiveness of this mechanism in halting legal proceedings requires further analysis. This study aims to examine the resolution of traffic accident cases through the restitution mechanism at the Bangli District Police and to determine the legal status of suspects after restitution is granted to victims. This research employs an empirical legal method. The results indicate that, in cases classified as minor and moderate traffic accidents whether involving minors or adults and resulting in minor injuries and material losses case resolution is achieved through the signing of a peace agreement between the suspect and the victim, leading to the termination of the legal process without litigation. It is concluded that restitution is an effective mechanism for resolving minor and moderate traffic accident cases; however, in cases of serious accidents, judicial proceedings remain necessary.